2021
DOI: 10.1055/a-1556-7784
|View full text |Cite|
|
Sign up to set email alerts
|

Autonomous Aldosterone Secretion as a Subclinical Form of Primary Aldosteronism: Pathogenesis and Clinical Significance

Abstract: In recent years, a substantial prevalence of primary aldosteronism (PA) has been demonstrated in both normotensive and mildly hypertensive cohorts. Consequently, a classic presentation of the syndrome, i. e. moderate-to-severe and resistant hypertension with concomitant hypokalemia, should be considered a tip-of-the-iceberg phenotype of a wide PA spectrum. Its entire range encompasses the non-classic clinical fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 64 publications
(110 reference statements)
0
9
0
Order By: Relevance
“…Such research has been accumulating in the case of MACS [ 18 ]. In our view, in patients with adrenal adenomas, AAS should be considered on par with mild hypercortisolemia, since the clinical consequences of both endocrinopathies may prove equally severe [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such research has been accumulating in the case of MACS [ 18 ]. In our view, in patients with adrenal adenomas, AAS should be considered on par with mild hypercortisolemia, since the clinical consequences of both endocrinopathies may prove equally severe [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol consisted of: recording patient history and physical examination, ECG, laboratory examinations, 24 h ambulatory blood pressure monitoring (ABPM), TTE, and measurement of common carotid arteries’ (CCAs) IMT. As previously reviewed, PA/AAS has been associated with HT, atherosclerosis, metabolic syndrome, and pathologic cardiac remodeling, which underlies the methodology of the study (respectively, ABPM, IMT, lipid profile, and TTE) [ 5 , 7 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 , 7 ]. It has been reported that autonomous aldosterone secretion as a subclinical form of PA accompanied by normotension increases the risk of cardiovascular disease, kidney disease, and osteoporosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aldosterone production that is not fully suppressed by sodium loading, AngII (angiotensin II) receptor (AT 1 R) blockade, or mineralocorticoid receptor activation 1,2 is recognized as dysregulated and independent of the renin-angiotensin system (RAS). This RAS-independent (autonomous) component of aldosterone production occurs within a spectrum of disorders that range from subclinical disease to overt primary aldosteronism (PA).…”
mentioning
confidence: 99%